Art + science now - Wilson, Stephen, 1944- (London : Thames & Hudson, 2010)
Introduction. Art, science + technology ## Molecular biology ## Living systems ## Human biology ## Physical sciences ## Kinetics & robotics ## Alternative interfaces ## Algorithms ## Information ## Conclusion. Cultural challenges in a techno-scientific age.
Formerly CIP.
boek
Keywords: Art and science; Art, Modern -- 21st century